A Fuzzy Model of Risk Assessment for Environmental Start-Up Projects in the Air Transport Sector - Polishchuk, Volodymyr; Kelemen, Miroslav; Gavurová, Beáta; Varotsos, Costas; Andoga, Rudolf; Gera, Martin; Christodoulakis, John; Soušek, Radovan; Kozuba, Jaroslaw; Blišťan, Peter; Szabo, Stanislav, Jr. (MDPI, 2019)
The purpose of this paper is to develop a fuzzy model of the risk assessment for environmental start-up projects in the air transport sector at the stage of business expansion. The model developed for the following software will be a useful tool for the risk decision support system of investment funds in financing environmental start-up projects at the stage of market conquest. Developing a quantitative risk assessment for environmental start-up projects for the air transport sector will increase the resilience of making risk decisions about their financing by the investors. In this paper, a set of 21 criteria for assessing the risk of launching environmental start-up projects in the air transport sector were formulated for the first time by presenting inputs in the form of a linguistic risk assessment and the number of credible expert considerations. The fuzzy risk assessment model, based on expert knowledge, uses linguistic variables, reveals the uncertainty of the input data, and displays a risk assessment with linguistic interpretation. The result of the paper is a fuzzy model that is embedded in a generalized algorithm and tested in an example risk assessment of environmental start-up projects in the air transport sector.
Fuzzy model hodnocení rizik pro environmentální start-up projekty v sektoru letecké dopravy
Keywords: air transport sector; decision support systems; environmental start-up project; expert systems; expert evaluation; fuzzy model; financial investments; decision-maker (DM); risk assessment; odvětví letecké dopravy; systémy pro podporu rozhodování; environmentální start-up projekt; expertní systémy; expertní hodnocení; fuzzy model; finanční investice; tvůrce rozhodnutí (DM); odhad rizika